The effects of selected metal ions on the stability of red cabbage anthocyanins and total phenolic compounds subjected to encapsulation process. Issue 6 (17th February 2017) - Ratanapoompinyo, Jakaphan; Nguyen, Loc T.; Devkota, Lavaraj; Shrestha, Pratiksha
Abstract: In this study, the stability of red cabbage anthocyanins and total phenolic compounds (TPC) co‐pigmented with various metals ions (Al 3+, Ca 2+, Fe 3+, and Sn 2+ ) under thermal treatment, spray drying, and storage was investigated. In general, it was found that the addition of metal ions accelerated the anthocyanins degradation but delayed TPC loss. Thermally treated samples experienced the highest loss of anthocyanins ( k  = 0.00173 min −1 ) when Sn 2+ was added whereas less detrimental effect ( k  = 0.00106 min −1 ) was observed with aluminum ion (Al 3+ ). During spray drying, metal ions, excluding Al 3+, induced significant losses of anthocyanins, ranging from 7.3% to 10.6%. However, TPC degradation of samples containing metal ions (18.6–22.2%) was less than control samples (26.7%). Similarly, degradation of anthocyanins during storage was more severe in samples containing Sn 2+ ( k  = 0.03602 week −1 ) than in control samples (0.00644 week −1 ) but TPC retention could be improved up to 6% by metal ions. Practical application: Anthocyanins in fruits and vegetables are important sources of natural colorants. Co‐pimentation with metal ions is a viable mechanism to impart the color and improve the stability of anthocyanins from plant and fruit extracts. However, its implications in anthocyanins treatments and preservation remain unknown. This study reported potential effects of metal ions on the stability of anthocyanins and other phenolic compounds under thermal treatment, encapsulation, and storage.